Mitigasi Cuaca Buruk Dan Pemasangan Penangkal Petir Sebagai Upaya Keselamatan Nelayan Kub Geronggong - Prativi Khilyatul Auliya; Fitroh Resmi; Septaviola Dini Utami; Mohammad Basuki Rahmat; Dimas Fanny Kusuma; Ilyasa' Maula Basharon (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Abstract: Many traditional fishermen in Indonesia still experience a decreasing income during the rainy season due to bad weather conditions. This community service activity aims to improve the safety of fishermen through the installation of lightning rods and education on bad weather conditions at sea. This activity was carried out in Segoro Tambak Village, Sedati District, Sidoarjo Regency, East Java. The participants in this activity are local fishermen who are members of the KUB Geronggong. The methods used in this activity include 1. Initial Survey; 2. Socialization; 3. Training Session; 4. Technology Application; and 5. Mentoring and Evaluation. The results of the pre-test and post-test showed that the fishermen's level of understanding increasing by 8%. Based on the questionnaire results, the majority of fishermen gave positive feedback of this activity. In terms of program assessment, 71.4% of participants stated that the material provided was very easy to understand, and 82.1% of participants considered the speakers' delivery to be very clear. The opportunity to ask questions was also considered sufficient by 64.3% of participants, while in terms of satisfaction, 85.7% of participants stated that they were very happy to participate in this activity. All participants (100%) stated that this activity increased their knowledge, improved their preparedness for bad weather, and encouraged the application of knowledge in their daily lives. Keywords: bad weather; fishermen; lightning rods; mitigation Abstrak: Masih banyak nelayan tradisional di Indonesia yang penghasilannya turun di musim penghujan karena kendala cuaca buruk. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan keselamatan nelayan melalui pemasangan alat penangkal petir dan edukasi cuaca buruk saat melaut. Kegiatan ini dilaksanakan di Desa Segoro Tambak, Kecataman Sedati, Kabupaten Sidoarjo, Jawa Timur. Mitra dari kegiatan ini merupakan nelayan lokal yang tergabung dalam Kelompok Usaha Bersama (KUB) Geronggong. Metode kegiatan meliputi 1.Survey Awal; 2.Sosialisasi; 3.Pelatihan; 4.Penerapan Teknologi; serta 5.Pendampingan dan Evaluasi. Dari hasil pre-test dan post-test didapati tingkat pemahaman nelayan meningkat sebesar 8%. Berdasarkan hasil kuesioner, mayoritas nelayan memberikan penilaian positif terhadap kegiatan ini. Pada aspek penilaian acara, sebanyak 71,4% peserta menyatakan materi yang diberikan sangat mudah dipahami, dan 82,1% peserta menilai penyampaian narasumber sangat jelas. Kesempatan bertanya juga dinilai sangat cukup oleh 64,3% peserta, sedangkan dari sisi kepuasan, 85,7% peserta menyatakan sangat senang mengikuti kegiatan ini. Seluruh peserta (100%) menyatakan kegiatan ini menambah pengetahuan, meningkatkan kesiapan menghadapi cuaca buruk, serta mendorong penerapan ilmu dalam kehidupan sehari-hari. Kata kunci: cuaca buruk; mitigasi; nelayan; penangkal petir